2021
DOI: 10.3390/cancers14010103
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Hepatocellular Carcinoma What Is the Evidence and Prevention Recommendations

Abstract: The increasing burden of hepatocellular carcinoma (HCC) emphasizes the unmet need for primary prevention. Lifestyle measures appear to be important modifiable risk factors for HCC regardless of its etiology. Lifestyle patterns, as a whole and each component separately, are related to HCC risk. Dietary composition is important beyond obesity. Consumption of n-3 polyunsaturated fatty acids, as well as fish and poultry, are inversely associated with HCC, while red meat, saturated fat, and cholesterol are related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 132 publications
(139 reference statements)
0
24
0
Order By: Relevance
“…This difference in gender distribution is thought to be closely related to hormone levels in men and their unhealthy lifestyles like overworking, staying up late and excessive drinking. Third, in terms of smoking status, studies have shown that smoking is a minor risk factor for HCC [ 30 , 31 ]. According to reports, smoking can increase the morbidity and mortality of HCC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference in gender distribution is thought to be closely related to hormone levels in men and their unhealthy lifestyles like overworking, staying up late and excessive drinking. Third, in terms of smoking status, studies have shown that smoking is a minor risk factor for HCC [ 30 , 31 ]. According to reports, smoking can increase the morbidity and mortality of HCC [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches limit the ability to parse out the combined impacts of obesity, smoking, and alcohol intake and increasing physical activity and plant-centered dietary patterns. Promisingly, changes in dietary patterns to increase plant-based foods can decrease the risk of liver cancer development by ~30–50%, although there is little information with regards to effects on HCC recurrence and mortality [ 82 ]. Detailed in the World Cancer Research Fund’s (WCRF) most recent report on diet, physical activity, and cancer, there is strong evidence that overweight or obesity, consumption of alcohol, and consuming foods contaminated with aflatoxins increases the incidence of liver cancer [ 83 ].…”
Section: Treatment Strategies For Obesity and Their Association With ...mentioning
confidence: 99%
“…Up to 40% of HCC cases can develop in NAFLD patients without cirrhosis, and NAFLD represents the most common cause of HCC in those without cirrhosis, accounting for 26.3% of 605 HCC cases without cirrhosis compared to 13.4% of 4539 of HCC cases with cirrhosis [11][12][13] . In the NAFLD spectrum, HCC incidence in patients with uncomplicated steatosis is estimated to be approximately 0.8-6.2 per 100 person-years, but is poorly reported in NASH due to its invasive histological nature [14][15][16] . However, it is reasonable to approximate the incidence of HCC in NASH to the median prevalence of simple steatosis and cirrhosis [13] .…”
Section: The Prevalence Of Hcc In Nafldmentioning
confidence: 99%